2022
DOI: 10.1111/wre.12557
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of ecological mowing combined with conventional mechanical or herbicide management on weeds in orange orchards

Abstract: In fruit crops like citrus, weeds coexist throughout their long cycle and can cause several yield losses. Ecological mowing (ECO) is an integrated weed management (IWM) option for citrus, as it produces an in-situ mulch that suppresses the weeds; however, there is a lack of information on the impacts of tree-row conventional (CONV) and ECO mechanical weed control when combined with residual or non-residual herbicides, or standard frequent mechanical (MECH) control. This study aimed to evaluate, for 3 years in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…A. tenella é uma espécie de difícil controle, pois além da propagação seminal pode multiplicar-se vegetativamente com facilidade por meio de gemas fisiologicamente ativas (Martinelli et al, 2022). Para maior controle da invasora, são necessárias medidas preventivas, como: a limpeza de equipamentos e implementos, evitando que sementes sejam transferidos de uma área infestada para outra não infestada.…”
Section: Resultsunclassified
“…A. tenella é uma espécie de difícil controle, pois além da propagação seminal pode multiplicar-se vegetativamente com facilidade por meio de gemas fisiologicamente ativas (Martinelli et al, 2022). Para maior controle da invasora, são necessárias medidas preventivas, como: a limpeza de equipamentos e implementos, evitando que sementes sejam transferidos de uma área infestada para outra não infestada.…”
Section: Resultsunclassified
“…However, a disadvantage of cover crops is that they cannot suppress intra-row weeds. To address this, Martinelli et al (2022) used mowers that cut the cover crop and move the residue to the intra-row area.…”
Section: Cover Crop Selectionmentioning
confidence: 99%
“…Several environmental factors, such as plant spacing, plant age, soil quality, plant arrangement, and prevailing weather conditions, contribute to the proliferation of weeds in proximity to citrus trees [12]. Analysis of interview data revealed that employing individuals for weed removal constitutes a substantial portion, ranging from 20% to 25%, of total production costs.…”
Section: Introductionmentioning
confidence: 99%